CONCEPT AND TERMINOLOGICAL PROBLEMS AND SIGNIFICANCE OF COMPETENT APPROACH TO EDUCATION TECHNOLOGY - Bekmurat Tulaev, Dustnazar Khimmataliev, Oybek Daminov, Jamshid Khakimov (International Journal of Advanced Science and Technology, 2020)
This article provides information on the conceptual and terminological problems of the competency approach to education, the essence of the concepts of competence, competence and professional competence, approaches by researchers, as well as the components of competence, the stages of success in professional competence in education.